Capture-recapture estimates of problem drug use and the use of simulation based confidence intervals in a stratified analysis. Issue 9 (13th August 2004) - Gemmell, Islay; Millar, Tim; Hay, Gordon
Abstract : Study objective: To establish the prevalence of problem drug use in the 10 local authorities within the Metropolitan County of Greater Manchester between April 2000 and March 2001. Setting and participants: Problem drug users aged 16–54 resident within Greater Manchester who attended community based statutory drug treatment agencies, were in contact with general practitioners, were assessed by arrest referral workers, were in contact with the probation service, or arrested under the Misuse of Drugs Act for offences involving possession of opioids, cocaine, or benzodiazepines. Design: Multi-sample stratified capture-recapture analysis. Patterns of overlaps between data sources were modelled in a log-linear regression to estimate the hidden number of drug users within each of 60 area, age group, and gender strata. Simulation methods were used to generate 95% confidence intervals for the sums of the stratified estimates. Main results: The total number of problem drug users in Greater Manchester was estimated to be 19 255 giving a prevalence of problem drug use of 13.7 (95% CI 13.4 to 15.7) per 1000 population aged 16–54. The ratio of men to women was 3.5:1. The distribution of problem drug users varied across three age groups (16–24, 25–34, and 35–54) and varied between the 10 areas. Conclusions: Areas in close geographical proximity display different patterns of drug use in terms of prevalence rates and age and gender patterns. This has important implications, both for future planning of service provision and for the way in which the impact of drug misuse interventions are evaluated.